What makes the heart of Boa constrictor (Squamata: Boidae) beat faster? - João Fabrício Mota Rodrigues; Roberta da Rocha Braga; Thaís Helena Alencar Ferreira; Estéfanni de Castro Pinheiro; Géssica dos Santos Araújo; Diva Maria Borges-Nojosa (Zoologia (Curitiba), 2015)
Body size is highly correlated with metabolism, which in turn influences physiological rates such as heart rate. In general, heart rate is negatively influenced by the size of animal's body, but there is insufficient data corroborating this pattern in snakes. This study evaluated how body size affects heart rate in captive Boa constrictor Linnaeus, 1758. We measured the heart rate of 30 snakes using digital palpation and evaluated how this rate is influenced by body mass and sex using Analysis of Covariance (ANCOVA). The heart rate of the snakes was 58.8 ± 6.7 bpm (beats per minute). Body size, estimated as log-transformed body mass, negatively influenced heart rate (F1,28 = 10.27, p = 0.003, slope = -0.00004, R2 = 0.27), but sex had no effect (F1,27 = 0.07, p = 0.80). In conclusion, this result corroborates the negative relationship between body size and heart rate for snakes and reinforces the influence of related metabolic characteristics, such as body size, on the physiological parameters of snakes.